The hip hop movement : from R&B and the civil rights movement to rap and the hip hop generation - Rabaka, Reiland, 1972- (Lanham, Maryland : Lexington Books, 2013)
Connecting classic rhythm & blues and rock & roll to the Civil Rights Movement, and classic soul and funk to the Black Power Movement, The Hip Hop Movement critically explores what each of these musics and movements' contributed to rap, neo-soul, hip hop culture, and the broader Hip Hop Movement. Ultimately, The Hip Hop Movement reveals that black popular music and black popular culture have always been more than merely "popular music" and "popular culture" in the con.
Introduction : Lift every voice and sing and rap -- [Part I] : The soundtracks of the Civil Rights movement, 1945-1965. Rhythm & blues : from classic rhythm & blues to rap's beats and rhymes ; Rock & roll : from classic rock & roll to rock rap -- [Part] II : The soundtracks of the Black Power movement, 1965-1980. Soul : from classic soul to neo-soul ; Funk : from P-funk to G-funk -- [Part] III : The soundtracks and social visions of the hip hop movement, 1980-present. The hip hop movement : from black popular music and black popular culture to a black popular movement.
Includes bibliographical references and index.
Print version record.
ebrary dda
English.
eBooks on EBSCOhost
Keywords: African Americans -- Music -- History and criticism; Popular music -- United States -- History and criticism; Popular music -- Social aspects -- United States -- History -- 20th century; Rap (Music) -- History and criticism; Hip-hop -- History and criticism; Musique populaire -- États-Unis -- Histoire et critique; Musique populaire -- Aspect social -- États-Unis -- Histoire -- 20e siècle.; Hip-hop -- Histoire et critique; MUSIC -- Genres & Styles -- Rap & Hip Hop; Minority Studies; Popular Culture; African-American Studies; African Americans -- Music; Hip-hop; Popular music; Popular music -- Social aspects; Rap (Music); United States; United States of America, USA; Popular music; Popular culture; Ethnic studies; Ethnic minorities & multicultural studies; Social & cultural history; Relating to African American people; Rap & Hip Hop; Music; 1900-1999; Criticism, interpretation, etc; History